The Diagnostic Value of Bedside Echocardiography and Lower Extremity Blood Vessels in Acute Pulmonary Embolism - Xinxin Xu; Jing Yuan; Xiaojie Pan; Guibin Du; Jiahui Zhang (Stem Cells International)
Objective. The study aimed to evaluate the value of bedside echocardiography (TTE) and lower extremity blood vessels in diagnosis and prognosis of acute pulmonary embolism (APE). Methods. A retrospective study was performed on 53 patients with APE diagnosed by CT pulmonary angiography (CTPA) (systemic systolic blood pressure was >90 mmHg at time of consultation, and systemic systolic blood pressure decreased by <40 mmHg compared with basic value in those with hypertension). All patients underwent TTE examination before treatment. The high-risk factors, clinical manifestations, laboratory tests, and prognosis were retrospectively analyzed. Results. The rate of PE-related deterioration (cardiopulmonary resuscitation, tracheal intubation, cardiogenic shock, and death) within 14 days of hospitalization in RVD was 28%, and mortality rate (sudden death) was 20%, compared with non-RVD (both 0%). TTE examination showed that RVD as a predictor of pulmonary embolism-related death had a sensitivity of 100%, a specificity of 58%, a positive predictive value of 20%, and a negative predictive value of 100%. Conclusions. (1) TTE has increasingly shown obvious advantages in diagnosis of APE. It can detect direct or indirect signs of pulmonary embolism, confirm diagnosis or suspected diagnosis, and noninvasively and dynamically observe hemodynamic changes of heart in patients with acute PTE before and after treatment.. (2) The PE-related exacerbation rate (28%) or mortality (20%) of APE patients in normotensive with RVD was higher without RVD (0%). RVD is an independent predictor of poor prognosis in normotensive acute PTE. TTE tests allow people to identify people at risk of early death. The short-term prognosis of patients without RVD was better (14 days).